Effect of Self Leadership and Work Motivation on the Performance of Private High School Teachers - Hattari, Nurfiani Sri; Ariyanto, Eny (Husnayain Business Review, 2023)
Purpose – The purpose of this research was to determine the effect of self-leadership on work motivation and its impact on the performance of private high school teachers in the West Jakarta Region II Education Sub-Agency. Methodology/approach – The method in this research is quantitative-causal research with a population of private high school teachers in the West Jakarta Region II Education Sub-dept., the sampling technique is snowball sampling with a sample size based on the theory of Hair et al, namely a minimum sample of 10 times the highest indicator. studied, so that the minimum sample that must be taken is 90 respondents, the minimum sample can be fulfilled because the sample collected in this study was 101 respondents. The data analysis method uses the Structural Equation Model-Partial Least Square (SEM-PLS). Findings – The results of the study stated that there was a positive -significant direct relationship between self-leadership on teacher performance, self-leadership on work motivation, and finally between work motivation on teacher performance. Meanwhile, motivation indirectly provides a mediating effect that complements the positive and significant relationship between self-leadership and teacher performance. Novelty/value – self-leadership that private high school teachers in the West Jakarta Region II Education Sub-dept have can support the emergence of work motivation and improve teacher performance, and work motivation can trigger an increase in teacher performance in a better direction.